Classroom Social Climate and Resilience in Secondary Education Students - Ana María Carroza-Pacheco; Benito León-del-Barco; Carolina Bringas-Molleda (European Journal of Investigation in Health, Psychology and Education, 2026)
Classroom social climate has become a factor of increasing interest within the educational field due to its potential influence on students’ well-being and adjustment. The present study focused on analysing the relationship between the different dimensions of classroom social climate and school resilience in a sample of 609 Spanish secondary education students aged between 11 and 17 years. The Classroom Social Climate Scale (CSC) and the School Resilience Scale (SRS) were used as data collection instruments. The data were analysed using correlations and linear regressions to examine associations while retaining the continuous nature of the resilience scores, complemented by multinomial logistic regressions to examine the probability of belonging to relatively low, medium, or high resilience resource groups. The results showed positive and significant associations between the dimensions Relationship, Interest and Communication with Teachers (RIC) and Group Cohesion and Satisfaction (GCS), and both the Internal Resources and External Resources dimensions of resilience. Linear regression models explained 17.2% and 18.0% of the variance in Internal and External Resources, respectively, whereas multinomial logistic regression models yielded Nagelkerke R2 values of 0.160 and 0.190. Furthermore, the GCS dimension appeared to show a stronger predictive contribution to the different dimensions of resilience, particularly for External Resources. The findings suggest that positive peer relationships and group cohesion constitute relevant contextual factors for the development of resilience during adolescence.